A study of mental depreciation and reference dependence. - Chen, Zeling. (2008)
This paper investigates the phenomenon called mental depreciation, which relates to the tendency for individuals to try to make their purchases worthwhile. Our research seeks to investigate if mental depreciation is influenced by product price reference points and disclosure formats.